The balanced scorecard as a strategic management tool in the textile sector - Patrícia Rodrigues Quesado; Salomé Marques; Rui Silva; Alexandrino Ribeiro (Administrative Sciences, 2022)
This paper aims to develop a proposal for implementing the Balanced Scorecard (BSC) in a large Portuguese company that operates in the textile sector, intending to promote its subsequent implementation. Through a qualitative research approach, a case study was carried out, using interviews, which allowed clarification of the strategic guidelines of the company under study. It was found that the organization under analysis has defined the main pillars for building the BSC: the mission, values and vision. It was also found that this is an organization with an open culture, concerned with developing efforts to create and implement tools that allow clear and fluid communication of strategic objectives in all sectors that incorporate it. It was also possible to assess that the BSC is a tool known to all employees. Everyone recognized that it would be a useful tool for improving organizational performance to meet strategic objectives. However, some factors were also found that can hinder its implementation, such as the availability of time, the organizational culture and everyone's commitment to the execution of this strategic management tool.
Keywords: 350; Balanced Scorecard; performance; strategic management; textile sector